2009
DOI: 10.1111/j.1582-4934.2009.00765.x
|View full text |Cite
|
Sign up to set email alerts
|

Dedifferentiation-derived cells exhibit phenotypic and functional characteristics of epidermal stem cells

Abstract: Differentiated epidermal cells can dedifferentiate into stem cells or stem cell-like cells in vivo. In this study, we report the isolation and characterization of dedifferentiation-derived cells. Epidermal sheets eliminated of basal stem cells were transplanted onto the skin wounds in 47 nude athymic (BALB/c-nu/nu) mice. After 5 days, cells negative for CK10 but positive for CK19 and β1-integrin emerged at the wound-neighbouring side of the epidermal sheets. Furthermore, the percentages of CK19 and β1-integrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Fu et al showed that normal human skin cells de-differentiated into stem cells in the presence of EGF. [30][31][32] Chaffer et al also demonstrated that CD44lo basal-like human mammary epithelial cells and the transformed epithelial cells could all spontaneously de-differentiated into CD44hi stem cells and CD44hi CSCs respectively, and the convertion of transformed epithelial cells to CSCs was more efficiently than the untransformed cells. 33 The conversion of bulk cancer cells into CSCs may be simpler due to the genomic instability of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Fu et al showed that normal human skin cells de-differentiated into stem cells in the presence of EGF. [30][31][32] Chaffer et al also demonstrated that CD44lo basal-like human mammary epithelial cells and the transformed epithelial cells could all spontaneously de-differentiated into CD44hi stem cells and CD44hi CSCs respectively, and the convertion of transformed epithelial cells to CSCs was more efficiently than the untransformed cells. 33 The conversion of bulk cancer cells into CSCs may be simpler due to the genomic instability of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…18) We previously found that the recombinant human epidermal growth factor could induce the reversion of differentiated epidermal cells into stem cells or stem cell-like cells in vivo. 19,20) Therefore, extrinsic factors in the cellular environment can influence the developmental fate of somatic epidermal keratinocytes, and we can achieve dedifferentiaton by remodeling a microenvirnoment composed of intrinsic and extrinsic cellular molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The dedifferentiation phenomenon of differentiated epidermal cells which dedifferentiated into stem cells or stem cell-like cells in the wound treated with recombinant human epidermal growth factor has already been reported [Fu et al, 2001]. In succedent researches, the model of epidermal cell dedifferentiation in vivo was constructed and dedifferentiation-derived stem cells were isolated [Zhang et al, 2010]. Thus, abundant epidermal stem cells can be generated using an efficient dedifferentiation process involving manipulation of the related pathways.…”
Section: Differentiated Epidermal Cells Regain the Ability To Regenermentioning
confidence: 99%